2009
DOI: 10.21101/cejph.a3509
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Use of Health Services Among Older Estonian Population

Abstract: The aim of the study was to analyse the self-reported use of health services among the older Estonian population, to explain the predictors of health care utilisation and to study access to health services in comparison with other population groups. In November 2005, a randomly sampled Estonian residents aged 15-64 (n=1264) and 65-74 (n=182) was personally interviewed using structured questionnaires. Of the respondents aged 65-74, 81% reported having visited a general practitioner (GP) or specialist during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…In the past 6 months, the findings showed that two-thirds of older adults used PHC services for medical health services, which differed from rates reported by Chou and Chi [7] study. In the past 12 months, the findings indicated that three-quarters of older adults used PHC services for medical health services, which is close to the Estonian study [9]. The high rate of medical service utilization in past 12 months compared with rate of utilization in the past 6-month and 1-month periods in the present study can be accounted for by the use of a longer time period.…”
Section: Discussionsupporting
confidence: 80%
“…In the past 6 months, the findings showed that two-thirds of older adults used PHC services for medical health services, which differed from rates reported by Chou and Chi [7] study. In the past 12 months, the findings indicated that three-quarters of older adults used PHC services for medical health services, which is close to the Estonian study [9]. The high rate of medical service utilization in past 12 months compared with rate of utilization in the past 6-month and 1-month periods in the present study can be accounted for by the use of a longer time period.…”
Section: Discussionsupporting
confidence: 80%
“…Survey for Health Ageing and Retirement in Europe and the English Longitudinal Study on Ageing; see Table 1). The samples were broadly similar except that our sample somewhat overrepresented females, and the Estonian subsample was somewhat better educated compared to a sample from an existing representative survey (Põlluste et al 2009). …”
Section: Participants and Proceduresmentioning
confidence: 74%
“…A study conducted in 2009 to analyze the self-reported use of health services among the older Estonian population showed that 81% of the respondents aged 65-74 had visited a GP or a specialist during the previous 12 months. The probability of visiting a GP was higher for those respondents who had health problems and lived in rural areas [35].…”
Section: Wwwjceionlineorgmentioning
confidence: 93%